2009
DOI: 10.1080/08039480802429458
|View full text |Cite
|
Sign up to set email alerts
|

Core features of suicide. Gender, age, alcohol and other putative risk factors in a low-incidence population

Abstract: The aim of the study was to elucidate some supposed core features of suicide through a study of suicide in a low-incidence population. The material covered all suicides and undetermined deaths 1945-2004 in the Faroe Islands (a low-incidence population) and the study made use of all available information. Results showed that suicide rate had been low since the Second World War. However, there was an increase throughout the 1970s and 1980s. Supposed core features of suicide, such as gender, marital status, forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…These adult health risk behaviors have also been associated with suicidality. Alcohol use (Dube et al., 2001; Flensborg‐Madsen et al., 2009; Joiner et al., 2007; Wang & Stora, 2009), illicit drug use (Dube et al., 2001; Fergusson et al., 2008; Hardt et al., 2008; Joiner et al., 2007), and smoking (Bronisch, Hofler, & Lieb, 2008; Schneider et al., 2009) are each highly associated with suicidal behaviors. Research on physical activity level is less clear; however, increased physical activity has been found to protect against suicidal behaviors among younger adults (Bjerkeset, Romundstad, Evans, & Gunnell, 2008; Kaplan, McFarland, & Huguet, 2007; Mukamal & Miller, 2009).…”
Section: Adult Health Risk and Protective Behaviorsmentioning
confidence: 99%
“…These adult health risk behaviors have also been associated with suicidality. Alcohol use (Dube et al., 2001; Flensborg‐Madsen et al., 2009; Joiner et al., 2007; Wang & Stora, 2009), illicit drug use (Dube et al., 2001; Fergusson et al., 2008; Hardt et al., 2008; Joiner et al., 2007), and smoking (Bronisch, Hofler, & Lieb, 2008; Schneider et al., 2009) are each highly associated with suicidal behaviors. Research on physical activity level is less clear; however, increased physical activity has been found to protect against suicidal behaviors among younger adults (Bjerkeset, Romundstad, Evans, & Gunnell, 2008; Kaplan, McFarland, & Huguet, 2007; Mukamal & Miller, 2009).…”
Section: Adult Health Risk and Protective Behaviorsmentioning
confidence: 99%
“…However, the pioneer suicide researcher Erwin Stengel (1964) estimated mental disorder was present in only 37% of those who complete suicide. Recent work (Wang & Stora, 2009) found evidence of psychiatric or drug disorders in 61% of suicides in the Faroe Islands, and work from China found a 'startlingly' low rate of mental disorder among completers (Law & Liu, 2008). Research in India also found a low rate of mental disorder, but a high rate of 'stresses stemming from social practices and perceptions' among completers (Vijayakumar et al, 2005;Jacob, 2008, Bastia & Kar, 2009).…”
Section: Notion: Not All Suicide Is the Results Of Mental Disordermentioning
confidence: 99%
“…Not all suicide is the result of mental disorder, and this can be substantiated by recent population (Wang & Stora, 2009;Law & Liu, 2008;Jacob, 2008, Bastia & Kar, 2009Maselko & Patel, 2009) and individual (Cheah et al, 2008;Pridmore & McArthur 2008, 2009Pridmore 2009) studies.…”
Section: Synthesismentioning
confidence: 95%
“…Thus the results of this study should be interpreted cautiously. Finally, this study only included several socio-environmental variables (i.e., rainfall, temperature, SEIFA, demographic variables), while other factors like personal and family history of mental health and psychiatric problems [58,59], local health service facilities [60], nutrition [61,62], religion [63,64], alcohol and drug use [65][66][67] may also influence mental health status and suicidal behaviours. However, the information on these variables was unavailable in this study.…”
Section: Discussionmentioning
confidence: 99%